Dviejų retų žodžių etimologijos - Karaliūnas, Simas (Baltistica, 1999)
Etymologies of two rare words Etymologies of two rare wordsLith. sùbinė (subinė̃, subìnė) “arse”, suben- exclusively in compounds, dial, sabinìkė “id.”, a diminutive, are the most obscure words regarding their orgin. The juxtaposition subìnkaulis “coccyx” : sabìnkaulis “id.” : bìnkaulis “lump, knob on a horse leg” makes it possible first of all to segment -kaulis (: káulas “bone”) and subin-, sabin-, bin- and then to divide the latter morphemes into prefixes su-, sa- and a root bin-. Thus sùbinė, suben- and sabinìkė consist most likely of prefixes su-, sa- “with” and the words *binė, *benė meaning “buttock”. Lith. dial, švašvà “daughter; sister” (< *svešrv-ā) evidently derives from IE *su̯ek̉rúH- “mother-in-law” and presents itself as a feminine counterpart of Lith. šẽšuras “father-in-law” < IE *su̯ék̉uro-.